KURIKULUM MERDEKA REIMAGINED: ADOPTING STORY SCIENCE FOR ENGLISH LITERACY LEARNING IN INDONESIAN MIDDLE SCHOOL (IAIN Syekh Nurjati Cirebon, 2022)
Abstract: In 2018 the Program for International Students Assessment (PISA) result indicates that Indonesia is at a very low literacy level (ranked 71st out of 77th countries). Furthermore, there is a declining trend (64 points) in 10 years in terms of the English Proficiency Index (EPI) as recorded by English First (EF). This fact, however, does not encourage us to move away from using the traditional pedagogy that is oriented toward the memorization of grammar and vocabulary. Recent research conducted by Sudimantara (2021) shows that there is a new alternative to teaching English academic writing without relying on grammar and vocabulary. In this study, Sudimantara (2021) develops a new pedagogy (multisensorial load reduction strategies) that activates the nonverbal components of language (rhythm, intonation, movement, emotion, and aesthetics), which are first processed in the right hemisphere, as the foundation of grammatical processing in the left hemisphere of the brain. This research, in fact, has generated a surprising result where the experimental group has made a highly significant learning improvement. Fletcher (2021) notes that humans do not only thinks in story but also recalls and reconstruct events in their memory in the form of story. The study was undertaken within a qualitative Research and Development framework. All research steps (Research and Information Collecting, Planning, Develop Preliminary Form of Product, and Evaluation) were completed. The result shows that this new digital literacy resource is applicable in the current curriculum context with some expected future improvement. This study is expected to generate more research on the development of brain-compatible digital literacy resources.